Instrumental meteorological records before 1850 - BRÖNNIMANN, S. (Institutional Knowledge at Singapore Management University, 2020)
Climate data are part of our cultural heritage. Enlightenment scientists initiated regular meteorological measurements in the seventeenth and eighteenth centuries, providing modern scientists a wealth of early weather and climate information from across the world. Very long temperature and rainfall series are widely used as a baseline for current changes and to study past climatic variations at regional scale. But records like these constitute only a subset of all measurements taken. We provide here a partial inventory of meteorological measurements made prior to around 1850. Numerous efforts by individuals, weather services, international projects, and the Atmospheric Circulation Reconstructions over the Earth Initiative (ACRE) form the basis of this inventory. Interest in such historical weather data is not new. Scientists in the early eighteenth century compiled meteorological data in their efforts to study and understand weather and climate in different parts of the world. Numerous inventories were compiled in the nineteenth and early twentieth centuries, and data were used for regional climate descriptions or isothermal maps. Although more recent attempts have been made to systematically compile eighteenth-century records, most historical inventories have been forgotten, mainly because the metadata from these inventories have never been digitized.